C.S. Lewis : The chronicles of Narnia - Abate, Michelle Ann, 1975-; Weldy, Lance (Houndmills, Basingstoke, Hampshire ; New York : Palgrave Macmillan, 2012)
"C. S. Lewis's seven-book series about the fictional land of Narnia has become an irrefutable classic. This collection of new, wide-ranging essays explores the past, present and future importance of the Narnia books, providing the most current, and some of the most cutting-edge, research about this popular fantasy series"--
Machine generated contents note: -- List of Contributors -- Introduction; M.A.Abate -- PART I: TEXTS AND CONTEXTS -- Collective Violence and Scapegoating in The Lion, the Witch and the Wardrobe; M.Green -- Turkish Delights and Sardines with Tea: Food in The Lion, the Witch, and the Wardrobe; R.Towns -- Elements of Arthur in Lewis's Caspian Trilogy; M.Corpora -- PART II: APPLICATIONS AND IMPLICATIONS -- 'All That Rot': Picturing Education in C. S. Lewis' Chronicles of Narnia; K.Dorwick -- War and the Liminal Space: Situating The Chronicles of Narnia in the 20th Century Narrative of Trauma and Survival; N.Lewis -- C. S. Lewis's Manifold Mythopoeics: Towards a Reconsideration of Eschatological Time in the Construction of the Post-World Wars Fantasy Novel for Children; J.M.Sommers -- PART III: ADAPTATIONS AND MEDIATIONS -- The Author, the Movie, and the Marketing: The Lion, The Witch and the Wardrobe and Early Reader Adaptations; R.Brock-Servias -- Textual Evolution(s) of Prince Caspian; L.Weldy -- Narnia Fans, Narnia Fan Cultures: C. S. Lewis and Digital New Media; N.Hamer -- PART IV: CONFLICTS AND CONTROVERSY -- Lewis and anti-Lewis: The Narnia Chronicles and Philip Pullman's His Dark Materials Trilogy; G.Bar-Hillel -- Dark Queen, Mixed-Race Kings, and Girls Whose Heads Have Something in Them: Lewis's Contemporary Stance on Race and Gender in The Chronicles of Narnia; D.Brown -- Boy-Girls and Girl-Beasts: The Gender Paradox in C.S. Lewis' Chronicles of Narnia; S.Rodriguez -- Annotated Bibliography -- Index.
Includes bibliographical references and index.
Keywords: Lewis, C. S. -- 1898-1963.; LITERARY COLLECTIONS / English, Irish, Scottish, Welsh; LITERARY CRITICISM / Children's Literature; JUVENILE NONFICTION / Literary Criticism & Collections